Early hatching enhances survival despite beneficial phenotypic effects of late-season developmental environments. Issue 1874 (14th March 2018) - Pearson, P. R.; Warner, D. A.
Abstract : Seasonal shifts in environmental conditions provide predictable cues to which organisms can respond in adaptive ways. For example, seasonal changes in temperature can induce phenotypes at different times of the year that have season-specific fitness benefits. Here, we tested the hypothesis that embryo responses to seasonal changes in thermal environments are adaptively matched to the timing of reproduction (environmental-matching hypothesis). We collected eggs of the brown anole lizard ( Anolis sagrei ) from early and late seasons, and exposed them to early and late thermal regimes that mimic nest temperatures. After measuring offspring morphology and performance, we quantified their survival in the field. Females had higher fecundity, but produced smaller eggs, early in the season compared with late in the season. Late-season eggs exposed to late thermal regimes had relatively high survival, but early-season eggs exposed to early thermal regimes had similar survival rates to those exposed to mismatched conditions. Late-season nest temperatures and late-season eggs produced offspring that were relatively large and fast runners. However, despite phenotypic benefits of late-season conditions, early-season hatchlings had greater survival in the field. Our results do not fully support the environmental-matching hypothesis but suggest that selection favours seasonal shifts in reproductive investment of mothers (high early-season fecundity) over plastic responses of embryos to seasonal environmental changes.